Falling film distillation assisted by a two-phase closed thermosyphon: contributions to modeling, control, optimization, and technoeconomic assessment of the pilot-scale unit - Battisti, Rodrigo (2021)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2021.